Virtue after Foucault: On refuge and integration in Western Europe - NASIR, MUHAMMAD ALI (SAGE PUBLICATIONS LTD, 2022)
I suggest that virtue ethics can learn from Foucault's critical observations on biopolitics and governmentality, which identify how a good cannot be disassociated from power and freedom. I chart a way through which virtue ethics internalizes this critical point. I argue that this helps address concerns that both virtue ethics and the critical scholarship inspired by Foucault otherwise ignore. I apply virtue ethics to the contexts of refugee arrival, asylum procedure, and immigrant integration in Western Europe; I then see how Foucault's critical thought provides a counterpoint to virtue ethics; I finally analyze how incorporating that critique allows virtue ethics to make sense of both the context and the stakes involved.
Keywords: Asylum; biopolitics; Foucault; integration; Maclntyre; refugee; virtue; virtue ethics; ASYLUM; GOVERNMENTALITY; IMMIGRATION; MANAGEMENT; MIGRATION; TRUTH